Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.342
|View full text |Cite
|
Sign up to set email alerts
|

Location-Dependent Impacts of Resource Inertia on Power System Oscillations

Abstract: Inertial responses are seen by the system as the injection or withdrawal of electrical energy, corresponding to a change of frequency. The inertia of a machine primarily contributes to the power system transient stability. Oscillations are always present in the bulk power system due to the electromechanical nature of the grid. Poorly damped oscillations may cause system instability. Thus, this paper aims to study inertia's impacts on system primary frequency response, in particular on system oscillation modes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was also observed that when a large portion of the total power system inertia is concentrated at one machine, the mean of the local RoCoF is significantly larger compared to when the power system inertia is equally distributed across all machines. In [6][7][8] authors propose the effect of uneven inertia distribution on local RoCoF, system small signal stability and transient stability on the ERCOT power system. They claimed that inertia contributes more to local frequency stability than the global (system) stability.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that when a large portion of the total power system inertia is concentrated at one machine, the mean of the local RoCoF is significantly larger compared to when the power system inertia is equally distributed across all machines. In [6][7][8] authors propose the effect of uneven inertia distribution on local RoCoF, system small signal stability and transient stability on the ERCOT power system. They claimed that inertia contributes more to local frequency stability than the global (system) stability.…”
Section: Introductionmentioning
confidence: 99%